Implementasi Kebijakan Pesantren Ramah Anak dalam Menanggulangi Bullying dan Kekerasan di Pesantren - Aminah, An An; Fadjarajani, Siti; Mulya, Gumilar; Marwan, Iis (PEMA, 2025)
The Child-Friendly Pesantren (Pesantren Ramah Anak/PRA) policy is a strategic initiative developed as an urgent response to the need for ensuring the protection and optimizing the potential of all students (santri) within Islamic boarding schools. This policy is particularly crucial given the inherent risks present in pesantren environments, which often involve a high incidence of violence, psychological pressure, and the absence of standardized child protection mechanisms. This study aims to comprehensively analyze the implementation of the PRA policy in modern pesantren settings, specifically focusing on internal regulations, caregiving models, learning approaches, and child protection management. The research employed a qualitative methodology using a case study design, conducted in two modern pesantren institutions that have actively embraced and implemented the PRA policy. The findings reveal that the policy’s implementation is actualized through three primary mechanisms: strengthening institutional collaboration, enhancing the capacity and competency of caregivers (musyrif), and improving the physical environment of the pesantren. However, the study also identified several significant operational challenges, including inconsistent supervision mechanisms, a deeply entrenched culture of seniority, and limited competencies among dormitory mentors (musyrif). Overall, this research underscores the imperative need to reinforce integrated and standardized Standard Operating Procedures (SOPs) for child protection. These SOPs must be aligned with the regulations set forth by both the Ministry of Religious Affairs (Kemenag) and the Ministry of Women’s Empowerment and Child Protection (KemenPPPA) to ensure the policy's effectiveness. Keywords: child-friendly pesantren, boarding school system, child protection, modern